Implikasi Erupsi Gunung Agung Terhadap Atraksi Wisata Air Di Daya Tarik Wisata Pantai Melasti, Desa Serangan, Kecamatan Denpasar Selatan, Kota Denpasar Bali - Novenia, Melinda; Pujani, Luh Putu Kerti (JURNAL DESTINASI PARIWISATA, 2019)
Tourism attraction by watersport on Melasti Beach Serangan from the beginning of December 2017 until mid- December 2017 the number of tourist visits has decreased to reach its lowest point of zero percent, and as for some of the tourist services business attractions are laid off in a certain period due to the eruption of Mount Agung. This research related to the implications of the eruption of Mount Agung on Melasti Serangan Beach is to find out how much the impact of the Mount Agung eruption on tourism on Serangan Island was located quite far from Mount Agung Consept that used to discuss the problems in this study is the concept of implication and concept of watersports. The method use qualitative data analysis techniques by conducting observations, in-depth interviews, and documentation. The technique of determining the informant is done by purposive sampling. Source of data obtained primary data sources in the form of in-depth interviews to the management of watersport tourism attractions in Melasti Serangan Beach and direct observation in the field. The secondary data source of this study is in the form of the Denpasar City tourism service website, such as the number of tourist visits to Serangan Island and previous research journals related to this study. The implication of the eruption of Mount Agung on watersport tourism attractions in Melasti Serangan Beach includes a direct influence which has resulted in a decrease in tourist visits. The influence referred includes changes in operational hours, but without shortening working hours. Almost all employees experience a policy of laying off a maximum of 20 days. A decrease in the number of tourist visits, especially in December. Similarly, the amount of income earned only reaches less than 50% of normal days.   Keywords : implication, eruption, management, watersport